Inter‐colony foraging area segregation quantified in small colonies of Adélie Penguins. (6th May 2020) - Ito, Kentaro; Watanabe, Yuuki Y.; Kokubun, Nobuo; Takahashi, Akinori
Abstract : Theoretical models on the movement of colonial animals predict that neighbouring colonies may segregate their foraging areas, and many seabird studies have reported the presence of such segregations. However, these studies have often lacked the appropriate null model to test the effect of neighbouring colonies on foraging areas, especially in small colonies or in short‐ranging species. Here, we examined the foraging areas of Adélie Penguins Pygoscelis adeliae from two neighbouring (2 km apart) colonies by using bird‐borne GPS loggers. The field study was conducted at Hukuro Cove colony (104 pairs) and Mizukuguri Cove colony (338 pairs) in Lützow‐Holm Bay, East Antarctica. We obtained GPS tracks for 504 foraging trips from 48 chick‐rearing Adélie Penguins and quantified the degree of overlap in the foraging areas between two colonies. We also produced simulated movement tracks by using correlated random‐walks assuming no inter‐colony competition and quantified the degree of overlap in the simulated foraging areas. Finally, we compared the results from real GPS tracks with those from simulated tracks to examine the effect of neighbouring colonies on Adélie Penguin movement. The results indicate that the degree of overlap was significantly smaller in real tracks than in simulated tracks. In real tracks, the foraging area of the smaller Hukuro Cove colony extended to the other side of the larger Mizukuguri Cove colony, unlike in simulated tracks. Consequently, we suggest that Adélie Penguins from two neighbouring colonies segregated their foraging areas and that the larger colony appeared to affect the foraging area of the smaller colony.